Selenide‐chitosan as High‐performance Nanophotocatalyst for Accelerated Degradation of Pollutants. Issue 17 (5th August 2020) - Ali, Nisar; Ahmad, Shehzad; Khan, Adnan; Khan, Saraf; Bilal, Muhammad; Ud Din, Salah; Ali, Nauman; Iqbal, Hafiz M. N.; Khan, Hammad
Abstract: Water pollution is one of the major global challenges today. Water bodies are contaminated by the heavy release of waste effluents of textile industries, which includes intensively colored dye pollutants. Herein, a ternary nanocomposite of bismuth copper selenide with small particle size and ternary metal selenide (TMS)‐chitosan microspheres (TMS‐CM) of the spherical porous surface were successfully synthesized. SEM, XRD, EDX, FTIR, and UV/Vis spectrophotometry analysis revealed the structural and morphological characteristics of the newly synthesized nanocomposites. SEM imaging showed the average diameter of TMS nanoparticle to be 33 nm. The crystal size was calculated as 6.33 nm and crystalline structure as orthorhombic using XRD findings. EDX confirmed the presence of Bi, Cu, and Se in the ternary nanocomposite. The bandgap of 1.8 eV was calculated from Tauc's plot for the TMS nanocomposite. SEM confirmed the successful synthesis of spherical TMS‐CM microspheres of porous surface morphology with an average size of 885.6 μm. The presence of chitosan microspheres in the synthesis of TMS nanocomposite was identified by FTIR spectral analysis. Furthermore, highly efficient photocatalytic degradation (up to 95.4%) of ARS was achieved within 180 min at pH 4.0 using 0.5 g of TMS‐CM in sunlight. The first‐order kinetic model fitted well to the photocatalytic decontamination of ARS using TMS‐CM with a rate constant of 6.1x10 −2 min −1 . The TMS‐CM gave attractive results and high efficiency in photocatalytic degradation of ARS dye after reusing and regeneration of up to seven successive cycles. The newly synthesized nanophotocatalyst could be efficiently used for the decontamination of dye polluted water from textile industries. Abstract : A ternary nanocomposite of bismuth copper selenide (TMS) with small particle size and ternary metal selenide‐chitosan microspheres (TMS‐CM) of the spherical porous surface was successfully synthesized. The TMS‐CM gave attractive results and high efficiency in the photocatalytic degradation of ARS dye after reuse of up to seven successive cycles. The newly synthesized nanophotocatalyst could be efficiently used for the decontamination of dye‐polluted water from textile industries.